2014
DOI: 10.1128/aem.02287-14
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Lactococcus lactis Reducing Properties to the Downregulation of a Major Virulence Regulator in Staphylococcus aureus, the agr System

Abstract: e Staphylococcus aureus is a major cause of food poisoning outbreaks associated with dairy products, because of the ingestion of preformed enterotoxins. The biocontrol of S. aureus using lactic acid bacteria (LAB) offers a promising opportunity to fight this pathogen while respecting the product ecosystem. We had previously established the ability of Lactococcus lactis, a lactic acid bacterium widely used in the dairy industry, to downregulate a major staphylococcal virulence regulator, the accessory gene regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…In addition, downregulation agr system linked with decreased reduction potential in environment, corresponding with downregulation sec expression [25]. The newly described se genes are not controlled by the agr system; on the contrary, some authors have reported that sell positively regulated by the agr regulatory system [12,31].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, downregulation agr system linked with decreased reduction potential in environment, corresponding with downregulation sec expression [25]. The newly described se genes are not controlled by the agr system; on the contrary, some authors have reported that sell positively regulated by the agr regulatory system [12,31].…”
Section: Resultsmentioning
confidence: 98%
“…Inhibition of S. aureus in fermented dairy products is dependent on properties of LAB that include acidification, the production of inhibitory molecules, change of redox potential, etc. [10,25]. Few studies have described the molecular mechanisms of interaction between S. aureus strains and different species of LAB [10,11,13,14,20,24,25].…”
Section: Introductionmentioning
confidence: 97%
“…It has been shown previously that L. lactis and other lactic acid bacteria (LAB) can influence the behaviour of S. aureus under different conditions (Nouaille et al 2014). In particular, it has been shown that in a cheese matrix, the accessory gene regulator (agr), the main regulatory system controlling S. aureus virulence factors such as enterotoxins, is affected by LAB; metabolism of S. aureus is also affected by LAB (Cretenet et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This feature is of great interest to control SE, although some SEs like SEA, whose expression is agr-independent, do not respond to this inhibitory activity. The mechanism involved in the inhibition is multifactorial and involves both the acidification and reducing properties of L. lactis (Nouaille et al 2014). Although the strain-dependency of this inhibitory activity has not been investigated in depth, one might consider that it is not highly strain-dependent.…”
Section: Inhibition Of Virulence Expression Of Pathogens By Lab Strainsmentioning
confidence: 99%